Modelling wildfire occurrence at regional scale from land use/cover and climate change scenarios. (November 2021) - Vilar, L.; Herrera, S.; Tafur-García, E.; Yebra, M.; Martínez-Vega, J.; Echavarría, P.; Martín, M.P.
Abstract: Wildfire occurrence is expected to increase in future climate and Land Use Land Cover (LULC) change scenarios, especially in vulnerable areas as the European Mediterranean Basin. In this study future probability of wildfire occurrence was estimated for a 20-year time period (2041–2060, centered on 2050) by applying a statistically-based regression model using LULC-derived contact areas with the forest cover (interfaces) as proxy for the human-related factor and a combination of Live Fuel Moisture Content and seasonal climate-related variables as predictors. Future wildfire occurrence was mapped under RCP 8.5 high emissions scenario in four Spanish regions with heterogeneous socioeconomic, LULC and natural fire-related characteristics at 1 km 2 target spatial resolution. Results showed increased wildfire probability in ∼19–73% of 1 km 2 cells, observing regional differences in the variable effects. This approach could be applied to other spatial scales offering tools for planning and management actions and to obtain different possible future scenarios. Highlights: A modelling framework for estimating future wildfire occurrence in LULC and climate change scenarios is described. LULC-derived interfaces and a combination of LFMC and seasonal climate-related variables were used as predictors. Expected changes will mainly increase wildfire occurrence with varied effects by analyzed region. Future regional wildfire predictions are useful to establish mitigation measures and for planning fire prevention actions.